Study of etiological determinants of undernutrition in undernourished children from Anganwadi - Patil, Mohan Anantrao (International Journal of Contemporary Pediatrics, 2017)
Background: Undernutrition is important childhood health problem especially in developing countries, closely related to childhood mortality and morbidity. It is multifactorial in origin. These determinants operate at different levels. Immediate causes operating at the individual level, underlying causes influencing households and communities and basic causes at society and policy makers level. In practice these determinants overlap considerably. Exact contribution of each determinant is difficult to assess. However knowledge of locally prevalent factors helps to fine tune interventional strategies. Methods: A prospective observational study was conducted in 100 consecutive undernourished children in the age group of 0-6 years, referred from Anganwadi center to tertiary care center. They were assessed for determinants of undernutrition. Determinants of undernutrition were categorized as per UNICEF conceptual framework of undernutrition. Results: Immediate determinants like Low birth weight, inadequate nutrition were significantly affected. Underlying determinants like quality and quantity of food, availability, access and utilization of health services, safe water supply and environmental sanitation, breastfeeding and complementary feeding, cultural taboos regarding food and health had remarkable association with undernutrition. Basic determinants like Women empowerment, maternal malnutrition and familial educational level were adversely affected. However determinants like food availability, access to food and socioeconomic status were satisfactory. Conclusions: Determinants of undernutrition in all three categories were differentially affected. Search for locally relevant determinants of undernutrition will be helpful to target intervention measures.